Digital futures for cultural and media studies - Hartley, John, 1948- (Hoboken : John Wiley & Sons, 2011)
An ambitious rendering of the digital future from a pioneer of media and cultural studies, a wise and witty take on a changing field, and our orientation to itInvestigates the uses of multimedia by creative and productive citizen-consumers to provide new theories of communication that accommodate social media, participatory action, and user-creativityLeads the way for new interdisciplinary engagement with systems thinking, complexity and evolutionary sciences, and the convergence of cultural and economic valuesAnalyzes the historical uses of multimedia from print, through broadcasting to the i.
Message -- What Message?Part I: Interdisciplinary Encounters; Part II: Madness, or Method?; Part III: Evolution of Homo Nuntius; Part IV: Fashion as 'the Message' of Homo Nuntius; Trickster the Entrepreneur; Cultural Science: System, Agency, Disruption, Change; New Firms; The 'A' Word; Distributed Talent; Lying Worm and Cry Baby; Structural Change; Bridging Culture and Science; 9 Paradigm Shifters; References; Acknowledgments; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Digital media -- Social aspects; Digital media -- Social aspects; Mass media; Social media; Social Science; SOCIAL SCIENCE -- Media Studies; Digital media -- Social aspects; Electronic books